Spatial variation in landscape evolution of the Xiaojiang Region, SE Tibetan Plateau - Wang, Dan; Dong, Youpu; Liu, Yi; Duan, Jiaxin (Frontiers in Earth Science, 2023)
Both tectonism and erosion are presumed to have influenced the landscape evolution of the Xiaojiang Region, SE Tibetan Plateau. However, it remains unclear which of these broad processes has played the dominant role in determining landscape form and evolution. To establish the relative importance of these two processes, we measured river longitudinal profiles and spatial variation in selected geomorphic indices within the region. We measured longitudinal profiles along four large rivers from north to south through the region and also measured drainage basin asymmetry, basin shape index, hypsometric integral, normalized stream-length gradient index, and the ratio of valley-floor width to valley height of 77 drainage basins in this region. The four longitudinal profiles reveal that tectonic activity decreases from north to south. Spatial variation in geomorphic indices reflects that the topography in the Xiaojiang Region may be primarily influenced by three major faults: the Xiaojiang fault, the Shiping fault, and the Qujiang fault, rather than influenced by precipitation, lithology, and drainage reorganization. The tectonic activity in different parts of the region shows that the northern part is the most active, the central part is the least active, and the southern part is moderately active. It is concluded that the spatial variation in landscape form and evolution of the Xiaojiang Region has been influenced more strongly by tectonics than by erosion.